Using Games: Role Play and Kahoot in English Language Teaching and Learning for Tourism Students - Tari, Nirmala; Safitri, Ni Putu Dianita (Akademi Komunitas MAPINDO, 2023)
To improve students' language learning and overall learning experience, the incorporation of games intoEnglish Language Teaching (ELT) has emerged as a potential pedagogical method. This abstract explores theuse of two types of game, namely role play and kahoot as a creative and successful teaching and learningEnglish, focusing on the effects on language proficiency, motivation, and engagement. Games are used in ELTas a dynamic and engaging platform that promotes a learner-centered atmosphere and stimulates studentparticipation and teamwork. The variety of possibilities accommodates to various learning styles and interests,combining conventional board games and digital kahoot language learning programs. Games establish anemotionally safe environment for language learners to explore with the target language without worryingabout making mistakes by incorporating aspects of enjoyment, competition, and challenge. This encouragingenvironment makes a big contribution to increasing students' self-assurance and lowering their anxiety, whichfosters a happy learning environment. Additionally, games can be altered to fit with particular language goals,allowing teachers to focus on different linguistic abilities like vocabulary, grammar, speaking, listening, andreading comprehension. The abstract also explains how games encourage situational learning and real-worldlanguage use. Role-playing games and simulations, for instance, let students put their language abilities incontext while immersing them in real-world situations. Meanwhile, kahoot can help students to enjoy thelearning process digitally. In conclusion, games present an effective and adaptable instrument to transformEnglish Language Teaching and Learning.Keywords: Games, Role Play, Kahoot, English Language Teaching, Learning